Laser Pulses Theory, Technology, and Applications - Peshko, Igor (IntechOpen, 2012)
This book discusses aspects of laser pulses generation, characterization, and practical applications. Some new achievements in theory, experiments, and design are demonstrated. The introductive chapter shortly overviews the physical principles of pulsed lasers operation with pulse durations from seconds to yoctoseconds. A theory of mode-locking, based on the optical noise concept, is discussed. With this approximation, all paradoxes of ultrashort laser pulse formation have been explained. The book includes examples of very delicate laser operation in biomedical areas and extremely high power systems used for material processing and water purification. We hope this book will be useful for engineers and managers, for professors and students, and for those who are interested in laser science and technologies.